Effectiveness of bridge-in, objective, pre-assessment, participatory learning, post-assessment, and summary teaching strategy in Chinese medical education: A systematic review and meta-analysis - Ma, Xingming; Zeng, Dequan; Wang, Jie; Xu, Kun; Li, Ling (Frontiers in Medicine, 2022)
The BOPPPS teaching strategy has been used recently in many medical courses as an improved and more practical pedagogy in China. Nevertheless, the effectiveness of this pedagogy has not been fully assessed in terms of knowledge and skill outcomes in medical education. This meta-analysis aimed to evaluate the effectiveness of the BOPPPS strategy compared with traditional lecture-based learning (LBL) in Chinese medical education. The English electronic databases of Web of Science, PubMed, Embase, and the Cochrane Library and the Chinese electronic databases of CNKI, CQVIP, Wanfang, and CBM were used to search the publications related to the BOPPPS teaching strategy before 6 Jun 2022. Eligibility publications were retrieved and the data were extracted by two researchers independently according to the predefined inclusion and exclusion criteria. Quality analysis was performed using the Cochrane risk-of-bias tool, and the meta-analysis was performed using RevMan 5.3 and StataSE. We retrieved 367 records and 41 studies with a total of 5042 medical students in the meta-analysis, which included 34 randomized controlled trials (RCTs) and 7 Cohort studies. In the cumulative meta-analysis, BOPPPS strategy significantly increased skill scores (SMD: 1.15, 95% CI: 1.00 to 1.30, P < 0.00001), knowledge examination scores (SMD: 1.56, 95% CI: 1.24 to 1.89, P < 0.00001), comprehensive ability scores (SMD: 1.22, 95%CI: 0.85 to 1.59; P<0.00001), and teaching satisfaction (OR: 3.64; 95%CI: 2.97 to 4.46; P<0.0001) compared to the LBL model among those medical students. Statistically similar results were obtained in the sensitivity analysis. These results showed that the BOPPPS method is an effective teaching strategy for Chinese medical students to improve skill scores, knowledge scores, comprehensive ability scores, and teaching satisfaction when compared with LBL in medical education. Because of the limited quantity and quality of the included studies, further rigorous studies are needed to conclude with more confidence.